2021
DOI: 10.1002/cne.25091
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain projection neurons target functionally diverse respiratory control areas in the midbrain, pons, and medulla oblongata

Abstract: Eupnea is generated by neural circuits located in the ponto‐medullary brainstem, but can be modulated by higher brain inputs which contribute to volitional control of breathing and the expression of orofacial behaviors, such as vocalization, sniffing, coughing, and swallowing. Surprisingly, the anatomical organization of descending inputs that connect the forebrain with the brainstem respiratory network remains poorly defined. We hypothesized that descending forebrain projections target multiple distributed re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 111 publications
2
14
0
Order By: Relevance
“…It is possible that improper ICV injection and local diffusion rather than ventricular distribution may account for the effects observed. Further, IA injection not properly administered may have affected surrounding regions that also control respiration ( Homma and Masaoka, 2008 ; Evans, 2010 ; Trevizan-Bau et al, 2021 ). Because central injection parameters were not verified explicitly, it is possible that off-target effects arising from galanin analog administration may have contributed to the outcomes observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that improper ICV injection and local diffusion rather than ventricular distribution may account for the effects observed. Further, IA injection not properly administered may have affected surrounding regions that also control respiration ( Homma and Masaoka, 2008 ; Evans, 2010 ; Trevizan-Bau et al, 2021 ). Because central injection parameters were not verified explicitly, it is possible that off-target effects arising from galanin analog administration may have contributed to the outcomes observed.…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have provided evidence that dyspnea is associated with activation of the insular cortex [ 53 ]. Meanwhile, Trevizan-Baú et al adopted holera toxin subunit B (CT-B) for the retrograde tracing of the neural regulation of breathing and found that insular exists alongside a great number of neurons with CT-B labeled [ 54 ]. Van et al used the pseudorabies virus (PRV) inoculation into the thyroarytenoid muscle, which participates in the breathing–swallowing coordination, showing that the PRV transfer from the peripheral to the swCPG, rCPG, hypothalamus, insular, and motor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of distributed post-inspiratory neurons during orofacial behaviors such as swallowing, vocalization or sniffing, which all require specific modulations of airway patency, is further supported by recent trans-synaptic tracing studies that identified a brainstem-wide pre-motor network that overlaps with key nodes of the primary respiratory pattern generation network, including the Kölliker-Fuse nucleus, BötC, pre-BötC and intermediate reticular nucleus (Kurnikova et al ., 2018; Takatoh et al ., 2021). Further, both the pre-BötC and the Kölliker-Fuse nucleus are specific targets of descending cortical projections (Yang et al ., 2020; Trevizan-Baú et al ., 2021) emphasizing that key nodes for the coordination of volitional orofacial behaviors with on-going breathing activities are likely to be anatomically distributed. Thus, the synaptic interplay of an extended and distributed brainstem circuit is required for the generation of cranial nerve motor patterns during eupnea as well as during the coordination of breathing with vital orofacial behaviors.…”
Section: Discussionmentioning
confidence: 99%